2021
DOI: 10.1371/journal.pgen.1009962
|View full text |Cite
|
Sign up to set email alerts
|

TM2D genes regulate Notch signaling and neuronal function in Drosophila

Abstract: TM2 domain containing (TM2D) proteins are conserved in metazoans and encoded by three separate genes in each model organism species that has been sequenced. Rare variants in TM2D3 are associated with Alzheimer’s disease (AD) and its fly ortholog almondex is required for embryonic Notch signaling. However, the functions of this gene family remain elusive. We knocked-out all three TM2D genes (almondex, CG11103/amaretto, CG10795/biscotti) in Drosophila and found that they share the same maternal-effect neurogenic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 105 publications
(160 reference statements)
3
9
0
Order By: Relevance
“…Therefore, amx is considered a component of the Notch signaling pathway. In the Drosophila genome, three paralogs of amx exist, namely biscotti ( bisc), amx , and amaretto ( amrt ) [ 52 ]. A study revealed that all three are maternal neurogenic genes, implying that each of them plays maternal roles that are essential for Notch signaling [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, amx is considered a component of the Notch signaling pathway. In the Drosophila genome, three paralogs of amx exist, namely biscotti ( bisc), amx , and amaretto ( amrt ) [ 52 ]. A study revealed that all three are maternal neurogenic genes, implying that each of them plays maternal roles that are essential for Notch signaling [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Drosophila genome, three paralogs of amx exist, namely biscotti ( bisc), amx , and amaretto ( amrt ) [ 52 ]. A study revealed that all three are maternal neurogenic genes, implying that each of them plays maternal roles that are essential for Notch signaling [ 52 ]. However, triple homozygotes of bisc, amx , and amrt are viable due to the maternal contribution of the corresponding proteins.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations